Coronavirus Disease 2019 is an Occupational Disease for Teachers: How to Support the Teacher Workforce - Alison K. Cohen; Lora Bartlett (NEW SOLUTIONS: A Journal of Environmental and Occupational Health Policy, 2026)
Analyzing a growing body of epidemiological research that considers coronavirus disease 2019 (COVID-19) as an occupational disease situates teaching (eg, pre-kindergarten, elementary, secondary) among the more vulnerable occupations. Teachers have experienced a higher risk of COVID-19 infection, hospitalization, death, and Long COVID than people from many other occupations. More research attending to occupational patterns and risk mitigation is needed. Taking an occupational epidemiology approach for teachers can inform a wide array of policy solutions, including school environment improvements that can support infection control, like air cleaning and ventilation, as well as supporting teachers experiencing disproportionate burdens of COVID-19, including those living with Long COVID.